COVID -19 and the Practice of Oral Medicine - A.H. Adedapo (Nigerian Dental Journal)
The pandemic of coronavirus disease (COVID-19) raises important concern to the practice of Oral Medicine. The practitioners of Oral Medicine are usually in close contact with the patient's biological specimens and it is important that the Oral Medicine teams should be protected from the risk of COVID disease. Every effort should be made by OM practitioners to ensure that new biosafety measures are mastered to reduce the spread of the novel virus and other viral agent spreading diseases.